2012
DOI: 10.1002/jsfa.5693
|View full text |Cite
|
Sign up to set email alerts
|

Digital image analysis of diverse Mexican rice cultivars

Abstract: Multivariate analysis indicated that the lateral side is the most sensitive for the classification of Mexican rice grains because of its color and morphometric characteristics. These results showed the application of image analysis for the future classifications of grains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
5
0
3
Order By: Relevance
“…There have been many studies conducted with digital image processing technology on food quality control and evaluation (Teena et al 2013;Jackman et al 2009;Du and Sun 2005b). In terms of rice quality evaluation (Camelo-Méndez et al 2012;Shimizu et al 2008), the studies have been mainly conducted on evaluation of rice appearance quality (Camelo-Méndez et al 2012), the ratio of broken rice (Van Dalen 2004), grain shape (Bjork et al 2009), rice varieties (Liu et al 2005) and chalkiness ratio and chalkiness degree. Image analysis has also been used to determinate the size distribution and percentage of broken kernels of rice (Van Dalen 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies conducted with digital image processing technology on food quality control and evaluation (Teena et al 2013;Jackman et al 2009;Du and Sun 2005b). In terms of rice quality evaluation (Camelo-Méndez et al 2012;Shimizu et al 2008), the studies have been mainly conducted on evaluation of rice appearance quality (Camelo-Méndez et al 2012), the ratio of broken rice (Van Dalen 2004), grain shape (Bjork et al 2009), rice varieties (Liu et al 2005) and chalkiness ratio and chalkiness degree. Image analysis has also been used to determinate the size distribution and percentage of broken kernels of rice (Van Dalen 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Méndez et al, 2013) was constructed for the interaction genotype/planting location and was based on the similarity percentage of K values obtained with Peleg's model. Groups were classified in 12 clusters.…”
mentioning
confidence: 99%
“…Peterson et al indicated that seed classification accuracy can be improved by using color images [25]. Image-based studies to discriminate between different varieties of rice grains [26,27], automatic classification of barley, oat, and rye [28], phenotyping of individual seeds [29], germination prediction of rice [30], and quality assessment of tomato seed [31,32] provide alternatives to manual inspection. However, the studies only focused on identification of species and not on the identification of healthy seeds or characterization of infected seeds along with inert materials.…”
Section: Introductionmentioning
confidence: 99%